Pengaruh Country Image Terhadap Minat Berkunjung Ke Korea Selatan Pada Komunitas Korean Jjang Garut - Ridian Gusdiana; Novie Susanti Suseno; Zikri Fachrul Nurhadi; Yulia Yulistina (Universitas Majalengka, 2021)
This research is motivated by the increasing number of Indonesian tourists visiting South Korea every year and the growing popularity of the phenomenon of South Korean popular culture in Indonesia. The purpose of this study is to explain the effect of country image on interest in visiting South Korea, explain the effect of cognitive country image on South Korea's affective country image, explain the respective effects of cognitive country image and affective country image on interest in visiting South Korea. This research approach is quantitative with hypothesis testing using path analysis technique. The subjects in this study were members of the Korean Jjang Community Garut with a total sampling of 77 people, so this research is a population study. The data collection uses an online questionnaire with the help of Google Form media. The results showed that country image consisting of cognitive country image and affective country image influenced the interest in visiting South Korea at the Korean Jjang Community Garut by 49.8%. If further reviewed, cognitive country image has an effect on the formation of South Korea's affective country image by 32.9%, then the influence of cognitive country image on interest in visiting South Korea is 17.4% and affective country image has an influence on interest in visiting South Korea by 32.4%. while the effect of cognitive country image through affective country image on interest in visiting South Korea is 16.2%.